Regaining autonomy, competence, and relatedness: Experiences from two Shared Reading groups for people diagnosed with cancer - Andersen, Tine Riis (Frontiers in Psychology, 2022)
This study explored 12 cancer patients’ experiences from participating in an online and on-site Shared Reading group for 16-weeks in Norway. Shared Reading is a practice in which prose and poetry is read aloud in small parts and discussed along the way. The study is a qualitative evaluation study with particular focus on how the participants experienced the reading group supported their life living with cancer. The study is mainly based on data collected from focus group discussions with the participants, which was analysed qualitatively through open coding. Four themes were identified: 1) open space 2) disconnecting through connecting 3) community 4) resonances and echoes. The reading group supported the participants’ lives with cancer in several ways: The reading group was, for example, experienced as a ‘special arena’ because it offered the participants a space for talking about their cancer, but also discussing any other topic. In that way, they were able to ‘balance life and cancer’. The engagement with the texts helped the participants to ‘disconnect’ from their illness, and the cognitive effort needed was beneficial for the participants as a form for ‘cognitive training’. Since many of the participants had, due to a low capacity of concentration and memory, completely stopped reading, the reading group also brought literature back into the participants’ lives. Furthermore, it was essential for the participants to feel they contributed to a community, to feel useful and valuable for others. The texts were also important, as some of them resonated strongly in the participants in the way of activating memories and connecting a text to own experiences. After a session a text could still have an impact as an ‘echo. The results are synthesised, discussed and supported through the framework of Self-determination theory and, more specifically, the basic psychological need theory. The reading group was experienced as a support for autonomy, competence, and relatedness, and promoted a feeling of intrinsic motivation that brought about new dimensions in the participants’ lives. The study wishes to increase our knowledge of the benefits of integrating Shared Reading groups as a low-cost, literature-based psychosocial support in cancer organisations.